On a pterosaur jaw from the Upper Jurassic of Tendaguru (Tanzania) - D. M. Unwin; W.-D. Heinrich (Fossil Record, 1999)
A short section of a mandibular symphysis is the first cranial fossil of a pterosaur to be reported from the Upper Jurassic of Tendaguru, Tanzania. It is made the holotype of a new dsungaripteroid pterosaur, Tendaguripterus recki n. gen. n. sp. All previously named pterosaur taxa from Tendaguru are shown to be nomina dubia. The pterosaur assemblage from Tendaguru contains a "rhamphorhynchoid", as well as the dsungaripteroid, and is similar in its systematic composition to other Late Jurassic pterosaur assemblages from Laurasia. The diversity and broad distribution of dsungaripteroids in the Late Jurassic suggests that the group was already well established by this time. Der erste Schädelrest eines Flugsauriers aus dem Oberjura von Tendaguru in Tansania wird beschrieben. Bei dem Fundstück handelt es sich um ein bezahntes Unterkieferbruchstück aus der Symphysenregion. Der Fund gehört zu einem neuen Taxon, das als Tendaguripterus recki n. gen. n. sp. bezeichnet und zur Überfamilie Dsungaripteroidea gestellt wird. Alle zuvor aus den Tendaguru-Schichten beschriebenen Taxa werden als nomina dubia angesehen. In Tendaguru sind Verteter der „Rhamphorhynchoidea“ und Dsungaripteroidea nachgewiesen. Diese systematische Zusammensetzung ist derjenigen anderer Flugsaurier-Vergesellschaftungen der späten Jura-Zeit ähnlich. Die Vielfalt und die weite Verbreitung der Dsungaripteroidea in Laurasia läßt darauf schließen, daß sich diese Flugsauriergruppe bereits in der späten Jura-Zeit erfolgreich durchgesetzt hatte. doi:10.1002/mmng.1999.4860020109